2022
DOI: 10.1177/10600280221134108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bleeding in Orthopedic Surgery With Perioperative Use of Serotonergic Antidepressants

Abstract: Background: The use of serotonergic antidepressants (SADs) is associated with an increase in bleeding, and their exposure during the perioperative period increases the potential bleeding risk in patients undergoing surgical operations. Objective: The purpose of this study was to compare the rates of bleeding between patients on perioperative SADs and those not on SADs in patients undergoing orthopedic surgical procedures. Methods: A retrospective cohort study was conducted with patients who were admitted to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previous research has shown that the use of serotonergic antidepressants is significantly linked to an increased likelihood of experiencing serious gastrointestinal bleeding, especially in those who are concurrently using NSAIDs. In a recent study conducted by Yang et al (2023) [ 19 ], it was shown that there was a threefold increase in the risk of receiving two or more units of packed red blood cells (PRBCs) transfusion. Comprehensive incidence research conducted an estimation of the absolute risk associated with serotonergic antidepressant use.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that the use of serotonergic antidepressants is significantly linked to an increased likelihood of experiencing serious gastrointestinal bleeding, especially in those who are concurrently using NSAIDs. In a recent study conducted by Yang et al (2023) [ 19 ], it was shown that there was a threefold increase in the risk of receiving two or more units of packed red blood cells (PRBCs) transfusion. Comprehensive incidence research conducted an estimation of the absolute risk associated with serotonergic antidepressant use.…”
Section: Discussionmentioning
confidence: 99%